Potensi Ekowisata Nusa Lembongan dalam Pengembangan Pariwisata Berkelanjutan Berwawasan Lingkungan - Ernawati Ernawati (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study examines the potential of Nusa Lembongan Ecotourism in developing sustainable tourism with an environmental perspective. The formulation of the problem studied in this research is “(1) What potential does Nusa Lembongan Ecotourism have in developing environmentally friendly sustainable tourism (2) How does Nusa Lembongan Ecotourism relate to environmentally sustainable tourism”. The method used is qualitative research with a descriptive approach to understand the phenomena experienced by the research subject. Data collection techniques include literature study and documentation. The findings show 1) The potential of Nusa Lembongan as one of the ecotourism-based tourist attractions offers a lot of amazing natural beauty that attracts the attention of tourists to visit and unwind by the hustle and bustle of the city air, not only local tourists but also many foreign tourists visit Nusa Lembongan because of the potential offered 2) Sustainable development is a strategy that limits the utilization of ecosystems and natural resources so that they are maintained. One of the new tourist destinations that is increasingly popular is the beauty of Nusa Lembongan Island.